(3CSeGA Njd GdYQH haQSGfgGs - (3CHh YHO Gddg eMeO Hf RjGO , GdeYQha HGHf GdCYQGHi,J (B231 (3g` s ((3eMeO eMehO Hf GdJdGejO GdJQcRi s)
(3ChdgG (B:s
(3bGd CHh GdHNJQi ReYI bGd (B: (3bGd QShd Gddg Udi Gddg Ydjg hSde (B: (3GQJHWhG gPg GdNjd aEfgG OYhI CHjce ESeGYjd , hcGfJ hMhTkG aOYi QHg aSQNG dg hjbGd Ef CUd Njd GdYQH ef aQS RhOg SdjeGf s
(3BNQgG (B:s
(3hbGd Ef GdZeGeI hGdUQjM hCUaGA hHfGJ CYQL fSd ddGLhGO hjQhi ajg GdZeGeI hGdUHhM hdGMb GHf eGdc GSe aQSg ecGf bGd ajg Je GdcJGH hGdMeO ddg s
(3HgG fXGe GdJYbjHIs
(3cJH HNW fSN Hg HYV edGeM GdNW GdeZQHis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B131 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B11s
Keywords: (3GddZIs